Physico-chemical Characterization, Classification and Quality Evaluation of Date Palm Fruits of some Moroccan Cultivars - Hasanaoui, A.; Elhoumaizi, M. A.; Hakkou, A.; Wathelet, B.; Sindic, M. (Journal of Scientific Research, 2010)
Fourteen native date cultivars from different oases and regions of Morocco, Tunisia and Algeria were examined for their approximate composition, water activity, and CIELAB parameters. Sugars were the predominant component in all studied date cultivars (~ 54.14 - 75.56 g/100g dry matter), followed by moisture content (~7.2 - 31.9%), along with small amount of protein (~1.9 - 3.3g/100g dry matter), fat (~ 0.1 - 0.44g/100g dry matter), and ash (~1.88 - 3.45g/100 g dry matter). Dates with early maturity had the highest water activity (0.78 - 0.87) in contrast to late maturing dates cultivars. In the Deglet Nour (Tunisia) and Aziza bouzid (Morocco) cultivars, sucrose is dominant, whereas, the majority of other cultivars were rich in fructose and glucose in comparable proportions. No significant changes were observed in the approximate composition of samples of different geographical origins. All cultivars show significant differences in color. The date with late maturity (from Assiane, Aziza bouzid and Boufeggous gharas locations of Morocco) were characterized by higher L*, a*, b* than the other date cultivars. Chemical composition of dates seems to be a good tool for fruit physiological and technological ability studies. Keywords: Date fruit; Reducing sugars; Moisture content; Maturity. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6062 J. Sci. Res. 3 (1), 139-149 (2011)